2006
DOI: 10.1590/s1806-83242006000400002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the quality of life of patients with oral cancer in Brazil

Abstract: This study performed a field trial of a Portuguese version of the University of Washington quality of life questionnaire (UW-QOL, 3rd version), aiming at appraising its ability to identify different patterns of health-related quality of life of patients with oral cancer in Brazil. Patients (N = 100) were interviewed as they were undergoing treatment for oral squamous cell carcinoma at a large Brazilian hospital ("Hospital das Clínicas", School of Medicine, University of São Paulo). The results were compared ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 14 publications
1
22
1
5
Order By: Relevance
“…The specific scores that were significantly higher in patients without cancer indicate the domains most affected by disease (pain, appearance, swallowing, chewing, speech, shoulders, taste and anxiety), which corroborates assessments done previously in the domestic scenario 18,19 . This observation also suggests that these were the quality of life domains that contributed most to the discriminant validity of the questionnaire.…”
Section: Discussionsupporting
confidence: 88%
“…The specific scores that were significantly higher in patients without cancer indicate the domains most affected by disease (pain, appearance, swallowing, chewing, speech, shoulders, taste and anxiety), which corroborates assessments done previously in the domestic scenario 18,19 . This observation also suggests that these were the quality of life domains that contributed most to the discriminant validity of the questionnaire.…”
Section: Discussionsupporting
confidence: 88%
“…The tongue was the predominant anatomical location (37.5%), also in accordance with recent studies (4,6, 8-10, 12,17,18). Some studies on oral cancer (2,3,5,14) have reported regularly reduced scores for the global status of quality of life for up to 5 years after treatment, chiefly when there is combination therapy (surgery plus radiotherapy, with or without chemotherapy). In this study most patients (56.3%) received combination therapy, there being no statistically significant differences in the final TOI (p=0.933), FACT-G (0.673) and FACT-HN (p=0.820) indices as for measurement of quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Although cure can be achieved in as many as 60% of the cases, this does not necessarily mean improvement of the quality of life, the latter being a great challenge for oncology (1). Questionnaires on quality of life in cancer are successfully used to assess health status, therapy efficacy and patients functional status and well-being (2). Because such assessments are not routinely done in the country, there is a paucity of Brazilian studies about this topic.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies strongly suggest that oral-related quality of life should be adopted as a standard criterion in hospital settings for the evaluation of oral cancer patients. 9 Oral cancer "campaigns", mouth self-examination and screening for oral cancer: any evidence of effectiveness?…”
Section: Risk Factors: What Is Different From the Already Known?mentioning
confidence: 99%